2005
DOI: 10.1007/s00268-005-7797-x
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Peptic Ulcer Treated by Simple Closure and Helicobacter Pylori Eradication

Abstract: Simple closure followed by Helicobacter pylori (Hp) eradication has become the most used procedure in perforated ulcer treatment. However, its efficacy and safety are still to be determined. To assess recurrence and re-perforation rates, and as a secondary objective, to analyze Hp infection rates in perforated ulcer patients and controls, we conducted a prospective study. Ninety-two consecutive patients (ages: 19-96 years) were operated on between 1996 and 2002, and treated by simple closure followed by Hp era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…H. pylori presence is not routinely screened preoperatively at most centers, although an increasing number of centers are beginning to do so. Efficacy and safety of eradication of H. pylori in treatment of perforated ulcers is still being examined [19]. Each of the patients discussed in previous case studies was treated empirically against H. pylori after development of ulcer perforation.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori presence is not routinely screened preoperatively at most centers, although an increasing number of centers are beginning to do so. Efficacy and safety of eradication of H. pylori in treatment of perforated ulcers is still being examined [19]. Each of the patients discussed in previous case studies was treated empirically against H. pylori after development of ulcer perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors found more common occurrence of H. pylori infection in patients with perforated duodenal ulcer, pyloric ulcer, and ulcer of the pyloric part of the stomach treated by suturing of the perforation and bacteria eradication than in subjects from the control group free of PUD (73.9% vs. 59.4%). The difference was not statistically significant [22,23]. They concluded that this slight difference did not support the thesis of H. pylori's role in the pathogenesis of PPU but the results obtained demonstrated that simple suturing of the perforated ulcer involved a low percentage of PUD relapses (2.6% during a 2-year follow-up) provided that H. pylori eradication was performed and NSAIDs were not used [22].…”
Section: Discussionmentioning
confidence: 99%
“…The difference was not statistically significant [22,23]. They concluded that this slight difference did not support the thesis of H. pylori's role in the pathogenesis of PPU but the results obtained demonstrated that simple suturing of the perforated ulcer involved a low percentage of PUD relapses (2.6% during a 2-year follow-up) provided that H. pylori eradication was performed and NSAIDs were not used [22].…”
Section: Discussionmentioning
confidence: 99%
“…Rostom, et al 22 , over wide review, concluded that any PPI drug was effective in reducing the incidence of peptic ulcer disease on chronic NSAID users; however, only misoprostol reduced the risk of complications like bleeding and perforation.…”
Section: Discussionmentioning
confidence: 99%